Outage Analysis of Train-to-Train Communication Model over Nakagami-m Channel in High-Speed Railway - Pengyu Liu; Xiaojuan Zhou; Zhangdui Zhong (International Journal of Antennas and Propagation)
This paper analyzes the end-to-end outage performance of high-speed-railway train-to-train communication model in high-speed railway over independent identical and nonidentical Nakagami-m channels. The train-to-train communication is inter-train communication without an aid of infrastructure (for base station). Source train uses trains on other rail tracks as relays to transmit signals to destination train on the same track. The mechanism of such communication among trains can be divided into three cases based on occurrence of possible-occurrence relay trains. We first present a new closed form for the sum of squared independent Nakagami-m variates and then derive an expression for the outage probability of the identical and non-identical Nakagami-m channels in three cases. In particular, the problem is improved by the proposed formulation that statistic for sum of squared Nakagami-m variates with identical m tends to be infinite. Numerical analysis indicates that the derived analytic results are reasonable and the outage performance is better over Nakagami-m channel in high-speed railway scenarios.